Ultrasonography findings of appendicular wall thickness in acute appendicitis and recurrent appendicitis with pathological correlation - Beniwal, Rajveer Singh; Thapa, Ragini (International Journal of Research in Medical Sciences, 2019)
Background: Appendicitis is among most common cause for acute abdominal pain requiring operative management. This study is to establish relationship between wall thickness of acute appendicitis and recurrent appendicitis with its pathological outcome. Methods: In this prospective study, 24 patients of acute appendicitis and 8 patients of recurrent appendicitis presenting as acute appendicitis were examined by High resolution Ultrasonography within 48 hrs of acute onset of symptoms following a detailed clinical examination. Alvarado scoring was done in all patients. Acute appendicitis and recurrent appendicitis were differentiated on the basis of clinical details and timeline of illness. Post operatively all specimens underwent gross and histopath examination and were divided into subgroups and tabulated as “early acute appendicitis”, “acute suppurative appendicitis” and “acute gangrenous Appendicitis”. Results: Wall thickness of acute appendicitis and recurrent appendicitis (presenting with acute onset of symptoms) were tabulated. Patients with wall thickness of <3mm had statistically significant higher prevalence of acute gangrenous appendicitis on pathological correlation. Patients with recurrent appendicitis had higher incidence of wall thickness <3mm, consequently increased incidence of acute gangrenous appendicitis. The value of z was 6.0715. The value of p is <0.00001. The result was significant at p <0.01 according to SPSS 16, which correlates well with findings. Conclusions: Wall thickness is an important indicator in the management of acute or recurrent appendicitis, wall thickness of <3mm or >3mm was decisive in patient management. Reduced wall thickness of appendix in patients with acute or recurrent appendicitis correlate with higher incidence of acute gangrenous appendicitis therefore are at higher risk of perforation and should be managed aggressively by surgical intervention to avoid complications.